Venkatanatha’s Engagement with Buddhist Opponents in the Buddhist Texts he Reused - Freschi, Elisa (Buddhist Studies Review, 2017)
Venkatanatha (1269—1370) was the most important systematiser of the Visistadvaita school of Vedanta. This article describes his use of Buddhist sources and shows how Venkatanatha reused Buddhist texts to a much more significant extent than his predecessors Yamuna and Ramanuja. The reused text-passages come mostly from the epistemological school of Buddhist philosophy (Dignaga, Dharmakirti and his followers) but there are important exceptions, attesting that Venkatanatha was also aware of Buddhist schools such as the Vaibhasikas, of whom only little is preserved today. Given that Buddhist philosophy was no longer an active presence in South India at the time of Venkatanatha, his interest in it must be due to factors other than his polemical agenda. Perhaps, his project of enlarging Visistadvaita Vedanta made him confront outsiders such as Buddhist thinkers and his intellectual interest in philosophy made him engage in a genuine confrontation with them.